Answer:
aₙ = 5*(1/5)^(n - 1)
Explanation:
The recursive relation for a geometric sequence is:
aₙ = aₙ₋₁*R
where R is the common ratio.
We could write this in a general form as:
aₙ = a₁*(R)^(n - 1)
where a₁ is the first term of the sequence.
In this case we know that:
R = 1/5
And that:
a₆ = 1/625
Then we can replace these values in the above relation to get:
a₆ = (1/625) = a₁*(1/5)^(6 - 1) = a₁*(1/5^5) = a₁*(1/3125)
1/625 = a1*(1/3125)
(3125/625) = a1 = 5
Then the formula will be:
aₙ = 5*(1/5)^(n - 1)